TOMOGRAFI ULTRASONIK UNTUK PENCITRAAN ALIRAN MULTI KOMPONEN - MULTI FASA - SALOMO HUTAGALUNG, SUTRISNO
The problem on how to estimate of multicomponen-multiphase flow of the combination among gas, oil and water has been of interest to the petroleum industry. As estimation of the composition of fraction components in the form of a cross sectional image reconstruction of multicomponents-multiphase can be made using the ultrasonic tomography. The computer program is needed for computing data of projection that can give an object image of various combination of mediums. The wave velocity in each medium and the time of flight are obtained from the measurements using transducer that placed around the pipe. Both the wave velocity and the time of flight are used as the base of getting an image object.. To obtain the projection data from many different directions, a transduser is used as transmitter and the others as the receiver, and the repeat this procedure until the last transduser as a transmitter. Data collection is constructed into parallel form, then with the use of filtered back projection algorithm an image can be reconstructed. The consider that the simulation flow regimes are the combination of sand, mud, water, oil and gas. The flow regimes are simulated in the matematical model of ultrasonic wave velocity distribution inside the pipe. System collecting data apllied 16, 32, 64 and 128 transduser and the resolution of image is limited by the number of data each projection and the number of its projection. In order to obtain high accuracy of resolution, it is needed to increase the number of transducer, alternatively to multiply the number of data obtained from measurement result of transducer using spline interpolation method. A consequence of increasing the number of transduser or multiply the number of data gives the longer computational time. The result to obtain relatif good resolution image when the transducer z 128 then the results of experiment for determining estimation of fraction composition has showed that 5.14 % for combination oil and water, 5.53 % for combination water and sand and 5.14 % for combination oil, water and sand.